2019
DOI: 10.1017/s0950268819000906
|View full text |Cite
|
Sign up to set email alerts
|

Attrition during pre-ART and ART time periods among adolescents enrolled in Integrated HIV Care Programme in Myanmar, 2005–2017

Abstract: Retaining adolescents (aged 10–19 years), living with HIV (ALHIV) on antiretroviral therapy (ART) is challenging. In Myanmar, 1269 ALHIV were under an Integrated HIV Care (IHC) Programme by June 2017 and their attrition (death and lost to follow-up) rates were not assessed before. We undertook a cohort study using routinely collected data of ALHIV enrolled into HIV care from July 2005 to June 2017 and assessed their attrition rates in June 2018 by time-to-event analysis. Of 1269 enrolled, 197(16%) and of 1054 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Our study observed a high rate of loss to follow up among adolescents compared to WHO 90-90-90 targets., Nevertheless, this rate of LTFU among adolescents was observed to be low compared to the study conducted in Myanmar (69%) [ 19 ]. However compared to our results, a low proportion of loss to follow up on ART was reported in a study conducted in Ethiopia (13.6%) [ 20 ].…”
Section: Discussionmentioning
confidence: 71%
“…Our study observed a high rate of loss to follow up among adolescents compared to WHO 90-90-90 targets., Nevertheless, this rate of LTFU among adolescents was observed to be low compared to the study conducted in Myanmar (69%) [ 19 ]. However compared to our results, a low proportion of loss to follow up on ART was reported in a study conducted in Ethiopia (13.6%) [ 20 ].…”
Section: Discussionmentioning
confidence: 71%
“…Retention was defined as children who were alive and on follow-up in the clinic at the end of the study period and children who were transferred out at any time during the study period. 11 …”
Section: Methodsmentioning
confidence: 99%